Local tourism in Malaysia: case study Kelantan / Fauzi Abdul Rahim - Abdul Rahim, Fauzi (1988)
Tourism: is concerned with all travellers visiting places other than their places of stay for various purposes such as leisure, business or a combination of the two. The type of tourist to be attracted to a destination will influence the nature of tourism development. Within the tourism development, an analysis of available resources to determine its potential and existing facilities will have to be known. The development would then be focused on the areas with the most potential according to tourism planning principles. Accordingly, development strategies can be drawn up to cater for the type of tourists desired.